Status of Bioactive Compounds from Bran of Pigmented Traditional Rice Varieties and Their Scope in Production of Medicinal Food with Nutraceutical Importance - Bhat, Farhan Mohiuddin; Sommano, Sarana Rose; Riar, Charanjit Singh; Seesuriyachan, Phisit; Chaiyaso, Thanongsak; Prom-u-Thai, Chanakan (Agronomy (Basel), 2020)
Consumption of pigmented rice as a staple food is rapidly increasing due to their healthy prospective and considered as functional food ingredients. Greater interest has been shown in many color rice varieties due to their multiple biological activities. The phenolic compounds have been found to consist of anthocyanidins, ferulic acid, diferulates, anthocyanins and polymeric proanthocyanidins. Anthocyanin is located in the bran layers of the rice kernel, while phenolic acids are mainly present in the bran layers of rice, existing as free, conjugated and bound forms. Keeping in view the several health benefits associated with the functional ingredients, such as anti-inflammatory, antioxidative and anticancer effects, pigmented rice is considered as a functional food and food ingredient in many Asian countries. The application and incorporation of bran into food products for the preparation of functional foods is increasing. Within the scope of this review, we highlighted the significant bioactive compounds from pigmented rice varieties and their potentials for medicinal and nutraceutical ingredients. The information provided from this could be of high benefit to the functional food industry and further research advance medicinal products.